2017
DOI: 10.1038/srep39705
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition affects insect susceptibility to Bt toxins

Abstract: Pesticide resistance represents a major challenge to global food production. The spread of resistance alleles is the primary explanation for observations of reduced pesticide efficacy over time, but the potential for gene-by-environment interactions (plasticity) to mediate susceptibility has largely been overlooked. Here we show that nutrition is an environmental factor that affects susceptibility to Bt toxins. Protein and carbohydrates are two key macronutrients for insect herbivores, and the polyphagous pest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
54
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 63 publications
2
54
3
Order By: Relevance
“…We previously found significant differences in molting rate, weight gain, and survival among the proprietary and WCRMO-1 diets (unpublished data). Research with lepidopteran insects has shown that the toxicity of Bt proteins can vary when protein to carbohydrate ratios are manipulated 38 , 39 . While lepidopteran and coleopteran insects are quite different, we may be able to draw parallels to this study.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found significant differences in molting rate, weight gain, and survival among the proprietary and WCRMO-1 diets (unpublished data). Research with lepidopteran insects has shown that the toxicity of Bt proteins can vary when protein to carbohydrate ratios are manipulated 38 , 39 . While lepidopteran and coleopteran insects are quite different, we may be able to draw parallels to this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the wild, radiation effects may be modified by other environmental stressors 76,77 . This synergistic effect may be widely found in nature; e.g., between nutrition and Bt toxins 78 . In the present study, the Ohara cabbage leaves contained lower radioactivity concentrations of cesium than the Baba cabbage leaves, but significant effects on development were detected only from Ohara.…”
Section: Discussionmentioning
confidence: 95%
“…It is highlighted that the bioassay protocols of the aforementioned works were different, for example using inoculation by immersion (Carrillo et al, 2015) or aspersion (Castrillo et al, 2011;Carrillo, Crane & Peña, 2013), keeping the insects during the bioassay time only on wet filter paper pieces, without food, which stressed beetles and compromised their immune system (Adamo et al, 2016;Deans et al, 2017). Based on this information, we consider that the bioassay method on avocado's sawdust artificial diet better simulates the interaction of the entomopathogen with the beetle and allows us to determine the effect on their cryptic ecology.…”
Section: Discussionmentioning
confidence: 99%